2019
DOI: 10.1007/s10995-019-02775-8
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Pregnancy and Neonatal Outcomes Among Marshallese Women Living in the United States

Abstract: Objective: Despite heterogeneity among Pacific Islanders, most studies aggregate them regardless of origin. Thus, limited information is available about perinatal outcomes among various subgroups of Pacific Islanders in the United States, including immigrants from the Republic of the Marshall Islands. We sought to evaluate perinatal outcomes among Marshallese women. Methods: We conducted a cross-sectional study of women with at least one singleton live birth between 1997 and 2013 in two Arkansas counties using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…Similar to other racial minority groups, NHPIs and Micronesian communities specifically experience substantial disparities in health and healthcare outcomes [14][15][16][17]. Maternal and perinatal outcomes are no exception [18][19][20][21][22]. For example, rates of cesarean delivery among Micronesian women are significantly higher compared to White women, even after adjusting for medical and sociodemographic confounders [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other racial minority groups, NHPIs and Micronesian communities specifically experience substantial disparities in health and healthcare outcomes [14][15][16][17]. Maternal and perinatal outcomes are no exception [18][19][20][21][22]. For example, rates of cesarean delivery among Micronesian women are significantly higher compared to White women, even after adjusting for medical and sociodemographic confounders [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal and perinatal outcomes are no exception [18][19][20][21][22]. For example, rates of cesarean delivery among Micronesian women are significantly higher compared to White women, even after adjusting for medical and sociodemographic confounders [19,20]. In addition, a study that compared indications for cesarean between Micronesian and White patients found that Micronesian women were over three times more likely to experience a cesarean delivery for more subjective medical indications (e.g., non-reassuring fetal heart tracing and arrest of labor) compared to more objective indications, a finding consistent with similar work examining cesarean delivery among Black women in the US [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, several studies of pregnancy hypertension and diabetes had to be excluded for not distinguishing between pre-existing and pregnancy-induced dysfunction. [ 20 , 88 ] While the main goal of this paper was not to compare Pacific Islanders’ risk for poor pregnancy/perinatal outcomes to those of other groups, but rather to identify gaps in the research, it should be noted that the majority of studies found that Pacific Islanders had higher prevalence, risk, or odds of having adverse outcomes compared to their white counterparts [ 27 32 , 34 – 39 , 41 49 , 51 , 52 , 58 – 65 , 67 – 73 ]. The underlying cause of these disparities needs further research but may be due to lack of healthcare access, discrimination, or other social determinants as have been reported among other U.S. minority/immigrant populations [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marshallese in the United States experience significant health disparities and report a high prevalence of diabetes, heart disease, and obesity (Hawley & McGarvey, 2015;Look et al, 2013;Mau et al, 2009;McElfish et al, 2017aMcElfish et al, , 2017bOkihiro & Harrigan, 2005;Schiller et al, 2012;Tung, 2012;US Department of Health & Human Services Office of Minority Health, 2015). Furthermore, Marshallese mothers are disproportionately likely to have poor maternal health outcomes compared to other racial and/or ethnic groups (Centers for Disease Control & Prevention, 2011;Chang et al, 2010Chang et al, , 2015Lavery et al, 2017;Nembhard et al, 2019aNembhard et al, , 2019bRao et al, 2006;Silva et al, 2006;Tsitas et al, 2015;Wartko et al, 2017). Pacific Islanders, and Marshallese specifically, are also underrepresented in research, which perpetuates and further obscures these health disparities impacting this vulnerable community (Compact of Free Association Community Advocacy Network, 2014;McGrath & Ka'ili, 2010;Palafox et al, 2002;Roehr, 2010).…”
Section: Introductionmentioning
confidence: 99%